İslam hukukunda Deyn’in Deyn karşılığında satımı - Kara, Yakup (My University, 2012)
Deyn, bey’, borç, vâde, kâlî, ayn, alacak, nesîe. ÖZET İSLAM HUKUKUNDADEYN’İN DEYN KARŞILIĞINDA SATIMI İslâm hukuku literatürü incelendiğinde, alım-satım akitleriyle ilgili hükümlerin ele alındığı bölümlerde bir alım-satım akdi yapılırken alınan mal ile malın bedelinin (semen) peşin ya da vadeli olması meselesinin de özenle incelendiği ve bu akitlerde mebi’in ve semen’in peşin yahut vadeli olması bakımından dört durumun ortaya çıktığı görülmektedir: Her ikisi peşin; Mal peşin bedel veresiye; Mal veresiye bedel peşin; Her ikisi de veresiye. Birinci şekil, insanlar arasında en çok gerçekleştirilen muamele olup bu muamelenin caiz olduğu hususunda alimler ittifak etmişlerdir. İkincisinin de Kur’an ve Sünnet’te caiz olduğuna işaret eden açık ifadeler vardır. Üçüncüsüne ise Hz. Peygamber tarafından bir takım tedbir ve ta’dillerle izin verildiğini görmekteyiz. Son olarak dördüncü şeklin ise (ki bu suret bizim de konumuzu teşkil etmektedir) hadislerde yasaklandığını görmekteyiz. İşte bu dördüncü şekil olan hem semenin ve hem de mebî’in veresiye olduğu muameleler fıkıh literatüründe “bey’u’d-deyn bi’d-deyn” diye ifade edilmektedir. “Bey’u’d-deyn bi’d-deyn” konusundaki tartışmalar ise “bey’u’l-kâlî bi’l-kâlî” hadisi etrafında cereyan etmektedir. Araştırmamızda “bey’u’d-deyn bi’d-deyn” konusuna dayanak teşkil eden mezkur hadisi ele alarak bu hadisin kapsamını, yani hangi tür muameleleri kapsadığını ve bu muamelelerin caiz olup olmadığı hususundaki İslam hukuk bilginlerinin görüşlerini vermeye çalışacağız. Deyn, bey’, borç, vâde, kâlî, ayn, alacak, nesîe. Dayn, bay’, dept, due date, kali, ‘ayn, claim, naseah.

THE SALE OF DEPT İN EXCHANGE FOR DEPT İN İSLAMİC LAW Whence the literature related with Islamic Law and those parts of this literature which deal with the issued provisions for trading are examined; we observe that whenever a trade contract is held; the commodity itself as well as the payment terms for the due payment (saman) of the commodity, in other words if the due payment would be done in cash or by a forward transaction, all is to be examined and studied diligently. As for the terms of payment; whether the payment would be done in cash or timed; we observe total four methods in any trade process held: Payment in cash and instant delivery, instant delivery and deferred payment, payment in cash and deferred delivery, both payment and delivery deferred. The first method mentioned above is the most common one applied by the parties and there is an agreement between the Islamic scholars on the matter. There are also clear arguments that the second method is also consistent with Quran and Sunnah both. In the third one we see that the Prophet (peace be upon him) let it done only under some amendments and cautions. As for the last method (which is our main objective) we clearly see that it is strictly forbidden in Hadiths. In Islamic Law literature the dealings related to this 4th method where payment (saman) and delivery of the commodity (mabi’in) are let deferred, is called bay’u’d-dayn bi’d-dayn. The arguments about bay’u’d-dayn bi’d-dayn take place within the Hadith called bay’u’l-kal bi’l-kal. In our search we will be investigating the subject bay’u’d-dayn bi’d-dayn within the framework of the above quoted Hadith as to what it contains and what kind of dealings it contains and also if these dealings are legitimate or not according to the opinions of the scholars of the Islamic Law.
Keywords: İslam Dini; İslam Hukuku